The story of Prophet Salih (AS) - Saniyasnain, Khan (Ajman, Goodword, 2024)
This delightful board book is a perfect gift for little children. The Quran story of Prophet Salih (AS) comes with charming illustrations and engaging text. The story has a moral in the end.